Fiber optics standard dictionary - Weik, Martin H (Chapman & Hall International Thomson Pub, 1997)
This invaluable reference dictionary covers every facet of fiber optics science and technology, a rapidly expanding area of interest. Coverage includes: the basic sciences related to all aspects of fiber optic signal generation, transmission and reception, including lightwave pulsing, modulation, propagation, dispersion, attenuation, and modal distribution; the full spectrum of life-cycle cradle-to-grave technology of fiber optic light sources, cables, and photodetectors, including design, development, manufacture, installation, operation, and maintenance of fiber optic systems and components; and the application of fiber optic systems to implement multimedia systems, including digital, analog, graphic systems, and their interconnection to wire, coaxial cable, microwave, radio, satellite and video transmission systems.